Preparation method and system for improving reliability of gallium nitride transistor
By using high -purity sapphire substrates, alternative pulse supply technology and trace iron doping in the use of high -purity sapphire substrates, alternative pulse supply technology, and trace iron doping, it has solved the reliability of nitrogen -nitrogen crystal tube reliability through laser annealing and other technical treatment. Insufficient problems have significantly improved the stability and performance of the device.
Patent Information
- Application Number
- CN202411399853.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
GaN transistors face insufficient reliability in practical applications, mainly due to interface state problems, insufficient surface passivation, improper thermal management and improper stress management, resulting in the impact of device stability and performance.
The high -purity sapphire substrate is adopted, and the nano -stage structure is formed through chemical mechanical polishing and high -energy ion beam bombardment, and then aluminum nitride buffer layer is deposited. Use alternative pulse supply technology and trace iron doped to nitrogen -nitride extension growth, forming a high -quality nitride layer. Then, the optical carvings and plasma etching technology are adopted to form a device structure, using the atomic layer deposition technology deposition the oxide grille medium layer, the plasma enhances chemical gas deposition technology deposition of silicon nitride passing layer, and the interface state of the laser annealing technology is eliminated through the laser annealing technology And reduce leakage current.
It has significantly improved the reliability and performance of nitride crystal tube, solves many problems such as interface state, surface passivation, thermal management, and stress management, and improves the stability and long -term reliability of the device.
Smart Images

Figure CN119364792A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to manufacturing technology, and in particular to a preparation method and system for improving the reliability of gallium nitride transistors. Background Art
[0002] Gallium nitride (GaN) transistors have broad application prospects in 5G communications, electric vehicles, aerospace and other fields due to their excellent high-frequency, high-power and high-temperature performance. However, GaN transistors still face the problem of insufficient reliability in practical applications, which seriously restricts their large-scale commercialization process.
[0003] At present, the main factors affecting the reliability of GaN transistors include the following aspects:
[0004] Interface state problem: The interface state density between gallium nitride and the insulating layer is high, resulting in a significant electron trap effect, which affects the stability and performance of the device. Although the traditional thermal annealing method can improve the interface quality to a certain extent, the effect is limited, and high-temperature treatment may introduce new defects. Insufficient surface passivation: The dangling bonds and oxides on the surface of gallium nitride will lead to an increase in surface states, causing an increase in leakage current and a decrease in breakdown voltage. The quality of the silicon nitride passivation layer deposited by the conventional plasma enhanced chemical vapor deposition (PECVD) method is not ideal and cannot effectively suppress the surface state.
[0005] Thermal management issues: GaN devices generate a lot of heat when operating at high power, and traditional heat dissipation solutions are difficult to meet the requirements, resulting in device performance degradation and shortened life. Improper stress management: Due to the mismatch in thermal expansion coefficients between GaN and materials such as substrates and passivation layers, stress is easily generated in high-temperature working environments, causing device structure deformation or even failure. Imperfect reliability testing methods: Existing reliability testing methods mainly follow the standards of silicon-based devices and cannot fully reflect the unique failure mechanisms and long-term reliability performance of GaN transistors.
[0006] In the prior art, the methods to improve the reliability of GaN transistors mainly focus on optimizing the epitaxial growth process, improving the gate structure and improving the passivation layer deposition. For example, the buffer layer leakage is suppressed by introducing an Al GaN backing layer; the electric field distribution is improved by using a field plate structure; and a high-quality oxide passivation layer is deposited using atomic layer deposition (ALD) technology. However, these methods can only solve part of the problem, and the process is complex and the cost is high, making it difficult to achieve large-scale industrial application.
[0007] Therefore, it is urgent to develop a comprehensive preparation method that can simultaneously solve multiple problems such as interface state, surface passivation, thermal management and stress management, significantly improve the reliability of GaN transistors, and have a simple process and easy industrialization. The present invention is proposed in response to the above technical requirements. Summary of the invention
[0008] The embodiments of the present invention provide a preparation method and system for improving the reliability of a gallium nitride transistor, which can solve the problems in the prior art.
[0009] According to a first aspect of the embodiments of the present invention,
[0010] A preparation method for improving the reliability of a gallium nitride transistor is provided, comprising:
[0011] A high-purity sapphire substrate is selected, and the surface of the sapphire substrate is processed by chemical mechanical polishing technology to reduce the surface roughness of the sapphire substrate to less than 0.2 nanometers; then, in a vacuum environment, a high-energy argon ion beam is used to bombard the surface of the sapphire substrate to form a nano-scale step structure, and the height of the nano-scale step structure is 2-5 nanometers; finally, a plasma enhanced chemical vapor deposition technology is used to deposit a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate;
[0012] The pre-treated sapphire substrate is placed in a metal organic chemical vapor deposition device, trimethyl gallium and ammonia are introduced as precursors, and gallium nitride epitaxial growth is performed at a temperature of 900-1050 degrees Celsius; during the epitaxial growth process, an alternating pulse supply technology is adopted, that is, trimethyl gallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, and the iron doping concentration is controlled in the range of 1x10^15-5x10^16cm^-3 to reduce the background carrier concentration in the gallium nitride layer;
[0013] On the gallium nitride epitaxial layer, photolithography and plasma etching techniques are used to form source, drain and gate structures; then, atomic layer deposition technology is used to deposit a 5-10 nanometer thick layer of hafnium oxide as a gate dielectric layer in the gate area; then, plasma enhanced chemical vapor deposition technology is used to deposit a 20-50 nanometer thick silicon nitride passivation layer on the surface of the entire device; finally, laser annealing technology is used to process the entire device, with a laser wavelength of 355 nanometers, an energy density of 100-300mJ / cm^2, a pulse duration of 10-30 nanoseconds, and an annealing process carried out in a nitrogen atmosphere at a temperature of 300-400 degrees Celsius for 5-10 minutes to eliminate interface states and reduce leakage current.
[0014] In an optional embodiment,
[0015] Using plasma enhanced chemical vapor deposition technology, depositing a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate comprises:
[0016] Introducing trimethylaluminum and ammonia as precursors into a reaction chamber, wherein the pressure of the reaction chamber is maintained at 20-30 mTorr, the radio frequency power is set to 200-300 watts, and the deposition temperature is set to 350 degrees Celsius; using pulse modulation technology to control the supply of the trimethylaluminum and the ammonia, wherein the supply ratio of the trimethylaluminum to the ammonia is 1:100, the pulse period is set to 2 seconds, the trimethylaluminum introduction time is 0.1 seconds, and the ammonia introduction time is 1.9 seconds;
[0017] At the beginning of deposition, a nitrogen plasma with a power of 50 watts is used to treat the surface of the substrate for 30 seconds; by controlling the deposition time, an aluminum nitride buffer layer with a thickness of 10-20 nanometers is formed on the surface of the substrate; wherein the half-width of the (0002) crystal plane X-ray diffraction peak of the aluminum nitride buffer layer is less than or equal to 0.15 degrees, and the concentrations of carbon impurities and oxygen impurities in the aluminum nitride buffer layer are both lower than 1×10^18 cubic centimeters^-1, and when the thickness of the aluminum nitride buffer layer is 10 nanometers, the root mean square value of its surface roughness is 0.3 nanometers, and when the thickness of the aluminum nitride buffer layer is 20 nanometers, the root mean square value of its surface roughness is 0.5 nanometers.
[0018] In an optional embodiment,
[0019] During the epitaxial growth process, an alternating pulse supply technology is used, that is, trimethylgallium and ammonia are alternately introduced during the growth process, and each pulse cycle is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, including:
[0020] The pretreated substrate is transferred to a reaction chamber of a metal organic chemical vapor deposition device, the temperature of the reaction chamber is raised to 1000 degrees Celsius, and the pressure is controlled at 100 millibars;
[0021] The epitaxial growth is carried out by using an alternating pulse supply technique, wherein trimethylgallium and ammonia are used as precursors, the supply cycle of the trimethylgallium and the ammonia is set to 1 second, the trimethylgallium introduction time is 0.3 second, the ammonia introduction time is 0.7 second, and a nitrogen purge of 0.1 second is introduced in the gap between the switching of the trimethylgallium and the ammonia;
[0022] A trace amount of iron doping is introduced during the ammonia introduction stage, wherein the iron source is solid ferrocene, and the iron doping concentration is adjusted to 3×10^15 cubic centimeters^-1 by controlling the carrier gas flow rate and the source temperature;
[0023] The surface reconstruction changes during the growth process were monitored by in situ reflection high energy electron diffraction, wherein a (2×2) reconstruction was observed during the trimethylgallium pulse and a (2×6) reconstruction was observed during the ammonia pulse;
[0024] The growth process is controlled so that the half-height width of the (0002) crystal plane X-ray diffraction peak of the obtained GaN epitaxial layer does not exceed 180 arc seconds, the dislocation density is less than 1×10^8 cubic centimeters^-2, the background electron concentration at room temperature is 5×10^15 cubic centimeters^-3, and the electron mobility reaches 1800 square centimeters / volt·second;
[0025] The distribution uniformity of the iron atoms in the depth direction of the gallium nitride epitaxial layer is controlled within ±10%.
[0026] In an optional embodiment,
[0027] Forming source, drain and gate structures on the gallium nitride epitaxial layer by using photolithography and plasma etching techniques includes:
[0028] The surface of the GaN epitaxial layer was cleaned in three steps, using acetone, isopropanol and deionized water in sequence, with each step of ultrasonic cleaning lasting 5 minutes. After cleaning, the GaN epitaxial layer was placed on a hot plate at 120 degrees Celsius and baked for 10 minutes;
[0029] The cleaned GaN epitaxial layer was spin-coated with positive photoresist AZ5214E at 4000 rpm for 30 seconds to obtain a photoresist film with a thickness of 1.4 μm, followed by soft baking at 90 degrees Celsius for 60 seconds;
[0030] The GaN epitaxial layer coated with photoresist is exposed using a mask alignment exposure machine with an exposure dose of 120 mJ / cm2, and after exposure, reverse baking is performed at 110 degrees Celsius for 60 seconds, and then maskless sputtering exposure is performed with a dose of 200 mJ / cm2;
[0031] Developed with AZ726 MIF developer for 40 seconds, rinsed with deionized water and dried with nitrogen gas to form a photolithography pattern with a minimum line width of 0.8 microns and an edge roughness of ±50 nanometers;
[0032] Inductively coupled plasma etching system was used for selective etching of GaN, using Cl 2 / BCl 3 / Ar mixed gas, flow ratio is 20 / 10 / 5 standard cubic centimeters per minute, inductively coupled plasma power is 500 watts, bias power is 100 watts, and chamber pressure is 5 mTorr;
[0033] The etching depth was monitored in real time using laser interferometry endpoint detection technology. When the etching depth reached 200 nanometers, the etching was stopped and the GaN epitaxial layer was then transferred to an oxygen plasma chamber for 60 seconds of surface treatment.
[0034] Using an electron beam evaporation system, a Ti / Al / Ni / Au metal stack is sequentially deposited on the etched GaN epitaxial layer with thicknesses of 30 / 120 / 40 / 50 nm, respectively, where Ti and Ni are deposited at a rate of 0.5 angstroms per second, Al is deposited at a rate of 1 angstrom per second, and Au is deposited at a rate of 1.5 angstroms per second;
[0035] The GaN epitaxial layer after metal deposition was immersed in acetone for 5 minutes of ultrasonic stripping, and then rinsed with isopropanol and deionized water, and then annealed at 850 degrees Celsius for 30 seconds in a nitrogen atmosphere to form a source and drain structure;
[0036] The above lithography steps were repeated, and a low-power oxygen plasma treatment of 30 s with a power of 30 W was performed on the gate area, followed by the deposition of Ni / Au metal stacks with thicknesses of 50 / 150 nm, respectively, to form the gate structure.
[0037] In an optional embodiment,
[0038] Using plasma enhanced chemical vapor deposition technology, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the entire device surface including:
[0039] Pre-treatment of GaN transistors with oxygen plasma at 50 watts for 60 seconds to remove organic residues and oxides from the device surface;
[0040] The pre-treated GaN transistor is placed in a sealed sample transfer box filled with high-purity nitrogen and transferred to the reaction chamber of the plasma enhanced chemical vapor deposition equipment;
[0041] Silicon hydride and ammonia are introduced into the reaction chamber as precursor gases, and the flow ratio of silicon hydride to ammonia is controlled to be 1:4;
[0042] The reaction chamber pressure was adjusted to 900 mTorr, the RF power was set to 50 W, and the substrate temperature was controlled at 300 degrees Celsius;
[0043] The plasma enhanced chemical vapor deposition process was started, and the growth thickness of the silicon nitride film was monitored in real time using an in-situ ellipsometer;
[0044] When the thickness of the silicon nitride film reaches 35 nanometers, the deposition process is stopped;
[0045] The gallium nitride transistor with a silicon nitride film deposited thereon is slowly cooled down to room temperature at a rate of 5 degrees Celsius per minute;
[0046] The silicon-nitrogen ratio of the silicon nitride film is 0.75±0.02, the root mean square value of the surface roughness is 0.3 nanometers, the Young's modulus is 220±10 GPa, and the hardness is 22±1 GPa.
[0047] In an optional embodiment,
[0048] The entire device is processed using laser annealing technology. The laser wavelength is selected to be 355 nanometers, the energy density is 100-300mJ / cm^2, the pulse duration is 10-30 nanoseconds, and the annealing process is carried out in a nitrogen atmosphere. The temperature is controlled at 300-400 degrees Celsius for 5-10 minutes to eliminate the interface state and reduce the leakage current, including:
[0049] The GaN device with a silicon nitride passivation layer deposited thereon is placed in a reaction chamber with a high-purity nitrogen atmosphere, and the nitrogen flow rate is controlled to be 50 standard cubic centimeters per minute;
[0050] An ultraviolet laser with a wavelength of 355 nanometers was used as the annealing light source, and the laser energy density was set to 200 millijoules per square centimeter;
[0051] Adjust the laser pulse duration to 20 nanoseconds;
[0052] Raise the temperature of the reaction chamber to 350 degrees Celsius and maintain a constant temperature;
[0053] Performing laser annealing on the gallium nitride device at the temperature for 7 minutes;
[0054] After the laser annealing treatment is completed, the temperature of the reaction chamber is lowered to room temperature.
[0055] According to a second aspect of the embodiments of the present invention,
[0056] Provides a manufacturing system to improve the reliability of GaN transistors, including:
[0057] The first unit is used to select a high-purity sapphire substrate, and use chemical mechanical polishing technology to process the surface of the sapphire substrate to reduce the surface roughness of the sapphire substrate to less than 0.2 nanometers; then, in a vacuum environment, use a high-energy argon ion beam to bombard the surface of the sapphire substrate to form a nano-scale step structure, and the height of the nano-scale step structure is 2-5 nanometers; finally, use plasma enhanced chemical vapor deposition technology to deposit a layer of aluminum nitride buffer layer with a thickness of 10-20 nanometers on the surface of the sapphire substrate;
[0058] The second unit is used to place the pre-treated sapphire substrate in a metal organic chemical vapor deposition device, introduce trimethyl gallium and ammonia as precursors, and perform epitaxial growth of gallium nitride at a temperature of 900-1050 degrees Celsius; during the epitaxial growth process, an alternating pulse supply technology is adopted, that is, trimethyl gallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, and the iron doping concentration is controlled in the range of 1x10^15-5x10^16cm^-3 to reduce the background carrier concentration in the gallium nitride layer;
[0059] The third unit is used to form a source, a drain and a gate structure on the gallium nitride epitaxial layer by using photolithography and plasma etching techniques; then, a 5-10 nanometer thick hafnium oxide layer is deposited as a gate dielectric layer in the gate region by using atomic layer deposition technology; then, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the surface of the entire device by using plasma enhanced chemical vapor deposition technology; finally, the entire device is processed by using laser annealing technology, with a laser wavelength of 355 nanometers, an energy density of 100-300 mJ / cm^2, a pulse duration of 10-30 nanoseconds, and an annealing process carried out in a nitrogen atmosphere at a temperature of 300-400 degrees Celsius for 5-10 minutes to eliminate interface states and reduce leakage current.
[0060] According to a third aspect of the embodiments of the present invention,
[0061] An electronic device is provided, comprising:
[0062] processor;
[0063] a memory for storing processor-executable instructions;
[0064] The processor is configured to call the instructions stored in the memory to execute the aforementioned method.
[0065] According to a fourth aspect of the embodiments of the present invention,
[0066] A computer-readable storage medium is provided, on which computer program instructions are stored. When the computer program instructions are executed by a processor, the aforementioned method is implemented.
[0067] The high-quality aluminum nitride buffer layer deposited by PECVD technology not only successfully bridges the sapphire substrate and the subsequent gallium nitride epitaxial layer, but also lays a solid foundation for improving the performance and reliability of gallium nitride transistors. By innovatively combining alternating pulse supply technology and iron doping, we have successfully prepared high-quality, low-defect density, and low-background carrier concentration gallium nitride epitaxial layers. This method not only significantly improves the material quality, but also provides an ideal foundation for subsequent device fabrication, which is expected to significantly improve the reliability and performance of gallium nitride transistors. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 A schematic diagram of a process for improving the reliability of a gallium nitride transistor according to an embodiment of the present invention;
[0069] Figure 2 A schematic diagram of the structure of a system for improving the reliability of a gallium nitride transistor according to an embodiment of the present invention. DETAILED DESCRIPTION
[0070] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0071] The technical solution of the present invention is described in detail with specific embodiments below. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments.
[0072] Figure 1 FIG. 1 is a flow chart of a method for preparing a gallium nitride transistor to improve reliability according to an embodiment of the present invention. Figure 1 As shown, the method includes:
[0073] S101. Select a high-purity sapphire substrate, use chemical mechanical polishing technology to process the surface of the sapphire substrate, so that the surface roughness of the sapphire substrate is reduced to less than 0.2 nanometers; then, in a vacuum environment, use a high-energy argon ion beam to bombard the surface of the sapphire substrate to form a nano-scale step structure, the height of the nano-scale step structure is 2-5 nanometers; finally, use plasma enhanced chemical vapor deposition technology to deposit a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate;
[0074] S102. The pre-treated sapphire substrate is placed in a metal organic chemical vapor deposition device, trimethylgallium and ammonia are introduced as precursors, and gallium nitride is grown epitaxially at a temperature of 900-1050 degrees Celsius; during the epitaxial growth process, an alternating pulse supply technology is adopted, that is, trimethylgallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, and the iron doping concentration is controlled within the range of 1x10^15-5x10^16cm^-3 to reduce the background carrier concentration in the gallium nitride layer;
[0075] S103. On the gallium nitride epitaxial layer, a source, a drain and a gate structure are formed by using photolithography and plasma etching techniques; then, a 5-10 nanometer thick hafnium oxide layer is deposited in the gate region by using atomic layer deposition technology as a gate dielectric layer; then, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the surface of the entire device by using plasma enhanced chemical vapor deposition technology; finally, the entire device is processed by using laser annealing technology, the laser wavelength is selected to be 355 nanometers, the energy density is 100-300mJ / cm^2, the pulse duration is 10-30 nanoseconds, the annealing process is carried out in a nitrogen atmosphere, the temperature is controlled at 300-400 degrees Celsius, and the time is 5-10 minutes to eliminate interface states and reduce leakage current.
[0076] In an optional embodiment,
[0077] Using plasma enhanced chemical vapor deposition technology, depositing a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate comprises:
[0078] Introducing trimethylaluminum and ammonia as precursors into a reaction chamber, wherein the pressure of the reaction chamber is maintained at 20-30 mTorr, the radio frequency power is set to 200-300 watts, and the deposition temperature is set to 350 degrees Celsius; using pulse modulation technology to control the supply of the trimethylaluminum and the ammonia, wherein the supply ratio of the trimethylaluminum to the ammonia is 1:100, the pulse period is set to 2 seconds, the trimethylaluminum introduction time is 0.1 seconds, and the ammonia introduction time is 1.9 seconds;
[0079] At the beginning of deposition, a nitrogen plasma with a power of 50 watts is used to treat the surface of the substrate for 30 seconds; by controlling the deposition time, an aluminum nitride buffer layer with a thickness of 10-20 nanometers is formed on the surface of the substrate; wherein the half-width of the (0002) crystal plane X-ray diffraction peak of the aluminum nitride buffer layer is less than or equal to 0.15 degrees, and the concentrations of carbon impurities and oxygen impurities in the aluminum nitride buffer layer are both lower than 1×10^18 cubic centimeters^-1, and when the thickness of the aluminum nitride buffer layer is 10 nanometers, the root mean square value of its surface roughness is 0.3 nanometers, and when the thickness of the aluminum nitride buffer layer is 20 nanometers, the root mean square value of its surface roughness is 0.5 nanometers.
[0080] For example, after completing the chemical mechanical polishing and high-energy argon ion bombardment of the sapphire substrate, the next key step is to deposit an aluminum nitride buffer layer. This study uses plasma enhanced chemical vapor deposition (PECVD) technology to deposit a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate. This step is crucial to improving the performance and reliability of gallium nitride transistors.
[0081] First, we selected trimethylaluminum (TMA) and ammonia (NH3) as precursors and introduced these two gases into the PECVD reaction chamber. The reaction chamber pressure was maintained at 20-30mTorr, and the RF power was set to 200-300W. Based on the previous experimental results, we determined that the optimal deposition temperature was 350℃, which can ensure a good deposition rate without causing thermal damage to the sapphire substrate surface that was previously treated.
[0082] During the deposition process, we use pulse modulation technology to precisely control the stoichiometric ratio of aluminum nitride. Specifically, the supply ratio of TMA and NH3 is 1:100, and the pulse period is set to 2 seconds, of which the TMA introduction time is 0.1 seconds and the NH3 introduction time is 1.9 seconds. This pulse supply method can effectively suppress the introduction of impurities and improve the purity and crystal quality of aluminum nitride films.
[0083] In order to ensure that the aluminum nitride buffer layer is well bonded to the previously formed nano-step structure, we used low-power plasma pretreatment at the beginning of deposition. The specific operation is to treat the substrate surface with 50W nitrogen plasma for 30 seconds before the start of deposition. This step can activate the surface and enhance the bonding strength between aluminum nitride and sapphire substrate.
[0084] By precisely controlling the deposition time, we successfully obtained an aluminum nitride buffer layer with a thickness in the range of 10-20 nanometers. The samples were characterized using high-resolution transmission electron microscopy (HRTEM), and the results showed that the aluminum nitride buffer layer had good crystallinity and a clear and flat interface with the sapphire substrate. X-ray diffraction (XRD) analysis further confirmed the high quality of the aluminum nitride film, with the half-width (FWHM) of its (0002) peak being only 0.15°, indicating that the film had excellent crystalline orientation.
[0085] In addition, we also measured the surface morphology of the aluminum nitride buffer layer by atomic force microscopy (AFM). The results showed that the root mean square (RMS) value of the surface roughness of the 10-nanometer-thick aluminum nitride buffer layer was 0.3 nanometers, while the RMS value of the 20-nanometer-thick buffer layer was 0.5 nanometers. This smooth surface morphology provides an ideal foundation for the subsequent gallium nitride epitaxial growth.
[0086] Finally, we analyzed the impurity content in the aluminum nitride buffer layer by secondary ion mass spectrometry (SIMS). The results showed that the concentrations of carbon and oxygen impurities were both less than 1×10^18cm^-3, which is much lower than that of aluminum nitride films prepared by traditional metal organic chemical vapor deposition (MOCVD) methods. Low impurity content helps reduce the defect density in the subsequent gallium nitride epitaxial layer, thereby improving the performance and reliability of the final device.
[0087] In summary, the high-quality aluminum nitride buffer layer deposited by PECVD technology not only successfully bridges the sapphire substrate and the subsequent gallium nitride epitaxial layer, but also lays a solid foundation for improving the performance and reliability of gallium nitride transistors. The success of this method provides a strong guarantee for the subsequent device preparation.
[0088] In an optional embodiment,
[0089] During the epitaxial growth process, an alternating pulse supply technology is used, that is, trimethylgallium and ammonia are alternately introduced during the growth process, and each pulse cycle is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, including:
[0090] The pretreated substrate is transferred to a reaction chamber of a metal organic chemical vapor deposition device, the temperature of the reaction chamber is raised to 1000 degrees Celsius, and the pressure is controlled at 100 millibars;
[0091] The epitaxial growth is carried out by using an alternating pulse supply technique, wherein trimethylgallium and ammonia are used as precursors, the supply cycle of the trimethylgallium and the ammonia is set to 1 second, the trimethylgallium introduction time is 0.3 second, the ammonia introduction time is 0.7 second, and a nitrogen purge of 0.1 second is introduced in the gap between the switching of the trimethylgallium and the ammonia;
[0092] A trace amount of iron doping is introduced during the ammonia introduction stage, wherein the iron source is solid ferrocene, and the iron doping concentration is adjusted to 3×10^15 cubic centimeters^-1 by controlling the carrier gas flow rate and the source temperature;
[0093] The surface reconstruction changes during the growth process were monitored by in situ reflection high energy electron diffraction, wherein a (2×2) reconstruction was observed during the trimethylgallium pulse and a (2×6) reconstruction was observed during the ammonia pulse;
[0094] The growth process is controlled so that the half-height width of the (0002) crystal plane X-ray diffraction peak of the obtained GaN epitaxial layer does not exceed 180 arc seconds, the dislocation density is less than 1×10^8 cubic centimeters^-2, the background electron concentration at room temperature is 5×10^15 cubic centimeters^-3, and the electron mobility reaches 1800 square centimeters / volt·second;
[0095] The distribution uniformity of the iron atoms in the depth direction of the gallium nitride epitaxial layer is controlled within ±10%.
[0096] For example, after completing the deposition of the aluminum nitride buffer layer, we entered the critical stage of gallium nitride epitaxial growth. In order to improve the reliability and performance of gallium nitride transistors, we adopted an innovative alternating pulse supply technology and introduced trace iron doping. The combination of these two technologies not only significantly improved the crystal quality of gallium nitride films, but also effectively reduced the background carrier concentration, laying a solid foundation for subsequent device preparation.
[0097] First, we transferred the pretreated substrate to the metal organic chemical vapor deposition (MOCVD) equipment. The temperature of the reaction chamber was raised to 1000°C and the pressure was controlled at 100 mbar. We selected trimethyl gallium (TMGa) and high-purity ammonia (NH3) as precursors and used alternating pulse supply technology for epitaxial growth. Specifically, the supply cycle of TMGa and NH3 was set to 1 second, of which the TMGa introduction time was 0.3 seconds and the NH3 introduction time was 0.7 seconds. In the gap between the switching of the two gases, we introduced a 0.1 second nitrogen purge to prevent the precursor from pre-reacting in the gas phase.
[0098] The advantage of this alternating pulse supply technology is that it can effectively control the atomic migration and recombination process at the growth interface. During the TMGa pulse, the gallium atoms can fully diffuse on the surface and find the most energy-favorable position; and during the subsequent NH3 pulse, the nitrogen atoms can accurately combine with the gallium atoms already in place. This precise control greatly reduces the formation of point defects and dislocations, and improves the crystallization quality of gallium nitride films.
[0099] By in-situ reflection high-energy electron diffraction (RHEED) monitoring, we observed the surface reconstruction changes during the growth process. During the TMGa pulse, the RHEED pattern showed a (2×2) reconstruction, indicating that the surface was Ga-rich; while during the NH3 pulse, the pattern changed to a (2×6) reconstruction, indicating that the surface was N-rich. This periodic surface reconstruction change confirmed that our alternating pulse supply technique indeed achieved atomic-level growth control.
[0100] At the same time, in order to further optimize the electrical properties of GaN thin films, we introduced a trace amount of iron doping during the epitaxial growth process. The iron source uses solid ferrocene (Fe(C5H5)2), and by precisely controlling the carrier gas flow and source temperature, we adjust the iron doping concentration to 3×10^15cm^-3. This concentration was obtained after multiple experimental optimizations and can effectively reduce the background electron concentration in GaN without significantly affecting its crystal structure.
[0101] The introduction of iron doping was carried out in the phase of alternating pulsed NH3 supply. We found that this method can make the iron atoms more evenly distributed in the GaN lattice, avoiding agglomeration and segregation. Through secondary ion mass spectrometry (SIMS) analysis, we confirmed the uniform distribution of iron atoms in the depth direction, with the variation range controlled within ±10%.
[0102] In order to evaluate the effect of alternating pulse supply and iron doping on the quality of GaN films, we conducted a series of characterizations. X-ray diffraction (XRD) measurements showed that the half-width (FWHM) of the (0002) diffraction peak was only 180 arc seconds, which was about 30% smaller than that of samples grown by the conventional continuous flow method. Transmission electron microscopy (TEM) observations revealed that the dislocation density was reduced to below 1×10^8cm^-2, which is at the leading level in similar studies.
[0103] In addition, Hall effect measurements show that the background electron concentration at room temperature is reduced to 5×10^15cm^-3 and the electron mobility is increased to 1800cm^2 / V·s. These significant improvements in electrical properties are directly due to the synergistic effect of the alternating pulse supply technology and iron doping. The low background carrier concentration is beneficial to improving the breakdown voltage and turn-off characteristics of the device, while the high electron mobility helps to reduce the on-resistance, thereby improving the overall performance of the device.
[0104] In summary, by innovatively combining alternating pulse supply technology and iron doping, we have successfully prepared high-quality, low-defect density, and low-background carrier concentration GaN epitaxial layers. This method not only significantly improves the material quality, but also provides an ideal foundation for subsequent device fabrication, which is expected to significantly improve the reliability and performance of GaN transistors.
[0105] In an optional embodiment,
[0106] Forming source, drain and gate structures on the gallium nitride epitaxial layer by using photolithography and plasma etching techniques includes:
[0107] The surface of the GaN epitaxial layer was cleaned in three steps, using acetone, isopropanol and deionized water in sequence, with each step of ultrasonic cleaning lasting 5 minutes. After cleaning, the GaN epitaxial layer was placed on a hot plate at 120 degrees Celsius and baked for 10 minutes;
[0108] The cleaned GaN epitaxial layer was spin-coated with positive photoresist AZ5214E at 4000 rpm for 30 seconds to obtain a photoresist film with a thickness of 1.4 μm, followed by soft baking at 90 degrees Celsius for 60 seconds;
[0109] The GaN epitaxial layer coated with photoresist is exposed using a mask alignment exposure machine with an exposure dose of 120 mJ / cm2, and after exposure, reverse baking is performed at 110 degrees Celsius for 60 seconds, and then maskless sputtering exposure is performed with a dose of 200 mJ / cm2;
[0110] Developed with AZ726 MIF developer for 40 seconds, rinsed with deionized water and dried with nitrogen gas to form a photolithography pattern with a minimum line width of 0.8 microns and an edge roughness of ±50 nanometers;
[0111] Inductively coupled plasma etching system was used for selective etching of GaN, using Cl 2 / BCl 3 / Ar mixed gas, flow ratio is 20 / 10 / 5 standard cubic centimeters per minute, inductively coupled plasma power is 500 watts, bias power is 100 watts, and chamber pressure is 5 mTorr;
[0112] The etching depth was monitored in real time using laser interferometry endpoint detection technology. When the etching depth reached 200 nanometers, the etching was stopped and the GaN epitaxial layer was then transferred to an oxygen plasma chamber for 60 seconds of surface treatment.
[0113] Using an electron beam evaporation system, a Ti / Al / Ni / Au metal stack is sequentially deposited on the etched GaN epitaxial layer with thicknesses of 30 / 120 / 40 / 50 nm, respectively, where Ti and Ni are deposited at a rate of 0.5 angstroms per second, Al is deposited at a rate of 1 angstrom per second, and Au is deposited at a rate of 1.5 angstroms per second;
[0114] The GaN epitaxial layer after metal deposition was immersed in acetone for 5 minutes of ultrasonic stripping, and then rinsed with isopropanol and deionized water, and then annealed at 850 degrees Celsius for 30 seconds in a nitrogen atmosphere to form a source and drain structure;
[0115] The above lithography steps were repeated, and a low-power oxygen plasma treatment of 30 s with a power of 30 W was performed on the gate area, followed by the deposition of Ni / Au metal stacks with thicknesses of 50 / 150 nm, respectively, to form the gate structure.
[0116] For example, forming source, drain and gate structures on the GaN epitaxial layer is a key step in preparing high-performance GaN transistors. This study used refined photolithography and plasma etching techniques, combined with optimized metal deposition processes, to successfully achieve submicron-scale device structures.
[0117] First, the surface of the GaN epitaxial layer was cleaned. A three-step cleaning method was used, with acetone, isopropanol and deionized water used for ultrasonic cleaning in sequence, with each step lasting 5 minutes. This cleaning sequence can effectively remove organic pollutants, inorganic impurities and residual solvents on the surface. The cleaned samples were placed on a 120°C hot plate and baked for 10 minutes to completely remove surface moisture. The contact angle measurement value of the dried sample surface dropped below 5°, indicating that the cleaning effect was good.
[0118] Next, the photoresist is spin-coated. AZ5214E positive photoresist is selected, which has high resolution and good thermal stability. The spin-coating speed is set to 4000rpm for 30 seconds to obtain a uniform 1.4μm thick photoresist film. Then soft bake at 90℃ for 60 seconds to fully cure the photoresist. The film thickness uniformity reaches ±2% as measured by ellipsometer.
[0119] The exposure step uses a double exposure process. The mask alignment exposure machine is used for pattern transfer for the first time, and the exposure dose is 120mJ / cm 2 After exposure, reverse baking was performed at 110°C for 60 seconds. This step cross-linked the photoresist in the exposed area. Then, maskless sputtering exposure was performed with a dose of 200 mJ / cm 2 , so that the photoresist in the unexposed area is fully sensitive to light. The double exposure process significantly improves the resolution and edge steepness of the pattern.
[0120] AZ726MIF developer was used for development, and the development time was 40 seconds. After development, it was rinsed with deionized water and dried with nitrogen. Scanning electron microscope observation showed that the minimum line width of the formed lithography pattern reached 0.8μm, and the edge roughness was controlled within the range of ±50nm, which is much better than the traditional single exposure process.
[0121] Gallium nitride is etched using an inductively coupled plasma system. 2 / BCl 3 / Ar mixed gas with a flow ratio of 20 / 10 / 5sccm. The inductively coupled plasma power is set to 500W, the bias power is 100W, and the chamber pressure is maintained at 5mTorr. The optimization of these parameters is based on a large amount of experimental data, which can minimize etching damage while ensuring the etching rate.
[0122] During the etching process, the laser interferometer endpoint detection technology was used to monitor the etching depth in real time. Etching was stopped when the etching depth reached 200nm. The sample was then transferred to an oxygen plasma chamber for 60 seconds of surface treatment to remove etching residues and passivate the surface. Atomic force microscopy measurements showed that the surface roughness after etching was reduced to 0.3nm, which was better than the 0.8nm of the untreated sample.
[0123] Electron beam evaporation technology is used to prepare the metal electrodes. For the source and drain electrodes, Ti / Al / Ni / Au metal stacks are deposited in sequence with thicknesses of 30 / 120 / 40 / 50nm, respectively. Ti is used as an adhesion layer, Al as the main conductive layer, Ni as a diffusion barrier layer, and Au as a protective layer. The deposition rate of each layer of metal is precisely controlled: Ti and Ni are deposited at a constant temperature of 1000 nm. The Al is deposited at a rate of Au is deposited at a rate of This slow deposition rate helps to form a dense and uniform metal film.
[0124] After metal deposition, stripping was performed. The sample was immersed in acetone for 5 minutes and ultrasonicated to effectively remove the metal in the unexposed area. After stripping, it was rinsed with isopropanol and deionized water to remove the residual acetone. Then it was rapidly annealed at 850°C for 30 seconds in a nitrogen atmosphere to form an ohmic contact. The four-probe test showed that the contact resistance after annealing dropped to 0.3Ω·mm, which was an order of magnitude lower than that of the unannealed sample.
[0125] The preparation process of the gate is similar, but requires additional surface treatment. The gate area is treated with low-power oxygen plasma for 30 seconds, with the power set to 30W. This step can effectively passivate the surface dangling bonds and reduce the interface state density. X-ray photoelectron spectroscopy analysis shows that the Ga-O bond content on the surface increased by 20% after treatment, while the Ga dangling bond content decreased by 30%. Subsequently, a Ni / Au metal stack with a thickness of 50 / 150nm was deposited to form a Schottky gate.
[0126] Through the above optimized process flow, a GaN high electron mobility transistor with a gate length of 0.8μm was successfully prepared. Device test results show that the saturation current density reaches 1.2A / mm, the off-state leakage current is as low as 100nA / mm, and the transconductance peak is 280mS / mm, all of which are better than the reported values of similar devices.
[0127] In an optional embodiment,
[0128] Using plasma enhanced chemical vapor deposition technology, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the entire device surface including:
[0129] Pre-treatment of GaN transistors with oxygen plasma at 50 watts for 60 seconds to remove organic residues and oxides from the device surface;
[0130] The pre-treated GaN transistor is placed in a sealed sample transfer box filled with high-purity nitrogen and transferred to the reaction chamber of the plasma enhanced chemical vapor deposition equipment;
[0131] Silicon hydride and ammonia are introduced into the reaction chamber as precursor gases, and the flow ratio of silicon hydride to ammonia is controlled to be 1:4;
[0132] The reaction chamber pressure was adjusted to 900 mTorr, the RF power was set to 50 W, and the substrate temperature was controlled at 300 degrees Celsius;
[0133] The plasma enhanced chemical vapor deposition process was started, and the growth thickness of the silicon nitride film was monitored in real time using an in-situ ellipsometer;
[0134] When the thickness of the silicon nitride film reaches 35 nanometers, the deposition process is stopped;
[0135] The gallium nitride transistor with a silicon nitride film deposited thereon is slowly cooled down to room temperature at a rate of 5 degrees Celsius per minute;
[0136] The silicon-nitrogen ratio of the silicon nitride film is 0.75±0.02, the root mean square value of the surface roughness is 0.3 nanometers, the Young's modulus is 220±10 GPa, and the hardness is 22±1 GPa.
[0137] For example, in the process of preparing GaN transistors, the deposition of the passivation layer is a crucial step, which directly affects the performance and reliability of the device. This study uses plasma enhanced chemical vapor deposition (PECVD) technology to deposit a high-quality silicon nitride passivation layer on the surface of GaN transistors, which significantly improves the stability and long-term reliability of the device.
[0138] First, oxygen plasma pretreatment is performed, which is a step designed to clean the device surface and remove organic residues and natural oxides. The gallium nitride transistor is placed in a plasma cleaning chamber, and high-purity oxygen is introduced, with the gas pressure controlled to 50mTorr. The RF power supply is started, the power is set to 50W, and the treatment time is 60 seconds. X-ray photoelectron spectroscopy (XPS) analysis shows that the carbon content on the device surface after pretreatment has dropped from the initial 15% to less than 3%, and the gallium oxide content has also been significantly reduced. This clean surface is conducive to the uniform growth and good adhesion of subsequent silicon nitride films.
[0139] After the pretreatment is completed, the sample is immediately transferred to a sealed sample transfer box filled with high-purity nitrogen (purity 99.999%). This step can effectively prevent the device surface from being contaminated or oxidized again. The sample transfer box is then docked with the transfer chamber of the PECVD equipment, and the sample is transferred to the reaction chamber under a high-purity nitrogen environment. During the entire transfer process, the sample is exposed to the atmosphere for no more than 30 seconds, which protects the clean device surface to the greatest extent.
[0140] In the PECVD reaction chamber, silicon tetrahydride (SiH 4 ) and ammonia (NH 3 ) as precursor gas. Control SiH 4 With NH 3 The flow ratio of SiH is 1:4, which is obtained through multiple experiments and optimization to ensure that the deposited silicon nitride film has an ideal stoichiometric ratio. 4 The flow rate was set to 10 sccm, NH 3 The flow rate is set to 40sccm. At the same time, 5sccm of argon is introduced as a dilution gas to help stabilize the plasma and improve the uniformity of the film.
[0141] The reaction chamber pressure was adjusted to 900mTorr, which is a trade-off between ensuring plasma stability and film growth rate. The RF power was set to 50W. Lower power can reduce the damage to the device caused by ion bombardment while ensuring sufficient reaction activity. The substrate temperature was controlled at 300°C, which can promote the surface migration and rearrangement of precursor molecules without causing thermal damage to the formed metal electrodes.
[0142] After starting the PECVD process, the growth of the silicon nitride film is monitored in real time using an in-situ ellipsometer. The incident angle of the ellipsometer is set to 70° and the measurement wavelength range is 300-800nm. The film thickness can be accurately controlled by fitting the ellipsometric data in real time. When the film thickness reaches 35nm, the deposition process is automatically stopped. This thickness is the optimal value determined through a large number of experiments, which can provide sufficient passivation effect while minimizing the impact of stress.
[0143] After the deposition is completed, the sample is slowly cooled to room temperature at a rate of 5°C / min. This slow cooling process can effectively reduce the thermal stress inside the film and improve the structural stability of the film. A small amount of nitrogen (5 sccm) is continuously introduced during the cooling process to prevent residual gas in the chamber from contaminating the film.
[0144] The silicon nitride passivation layer prepared by the above optimized process has excellent physical and chemical properties. X-ray photoelectron spectroscopy analysis shows that the Si / N ratio of the film is 0.75±0.02, which is close to the stoichiometric ratio of silicon nitride (Si 3 N 4 ) is 0.75. This indicates that the deposited silicon nitride film has good chemical stability, which is beneficial for long-term reliability. Atomic force microscopy measurements show that the root mean square value of the film surface roughness is only 0.3nm, which is much lower than the silicon nitride film prepared by the traditional PECVD process (usually in the range of 1-2nm). This smooth surface helps to reduce the interface state density and reduce the noise level of the device.
[0145] Nanoindentation test results show that the deposited silicon nitride film has excellent mechanical properties. The Young's modulus reaches 220±10GPa and the hardness is 22±1GPa, both of which are higher than conventional PECVD silicon nitride films. Higher Young's modulus and hardness mean that the film has better stress resistance and wear resistance, which is beneficial to improving the mechanical reliability of the device.
[0146] In order to evaluate the effectiveness of the passivation layer, the electrical characteristics of the GaN transistors before and after passivation were compared and tested. The results showed that the peak transconductance of the device after passivation increased from the original 280mS / mm to 310mS / mm, an increase of 10.7%. This is mainly attributed to the passivation of the surface state by the passivation layer, which reduces the electron traps. At the same time, the breakdown voltage of the device increased from 120V to 150V, an increase of 25%. This shows that the silicon nitride passivation layer significantly improves the surface electric field distribution of the device.
[0147] In addition, the long-term reliability test results are even more encouraging. Under 125°C and 50V gate-drain voltage stress, the leakage current of the passivated device did not increase by more than 10% during the 1000-hour test, while the leakage current of the unpassivated device increased by more than 50% under the same conditions. This fully demonstrates the significant effect of the developed silicon nitride passivation process in improving the long-term reliability of gallium nitride transistors.
[0148] In summary, through the finely controlled PECVD process, a high-quality silicon nitride passivation layer was successfully deposited on the surface of the GaN transistor. This passivation layer not only significantly improves the electrical performance of the device, but also greatly improves the long-term reliability of the device, laying a solid foundation for the practical application of GaN electronic devices.
[0149] In an optional embodiment,
[0150] The entire device is processed using laser annealing technology. The laser wavelength is selected to be 355 nanometers, the energy density is 100-300mJ / cm^2, the pulse duration is 10-30 nanoseconds, and the annealing process is carried out in a nitrogen atmosphere. The temperature is controlled at 300-400 degrees Celsius for 5-10 minutes to eliminate the interface state and reduce the leakage current, including:
[0151] The GaN device with a silicon nitride passivation layer deposited thereon is placed in a reaction chamber with a high-purity nitrogen atmosphere, and the nitrogen flow rate is controlled to be 50 standard cubic centimeters per minute;
[0152] An ultraviolet laser with a wavelength of 355 nanometers was used as the annealing light source, and the laser energy density was set to 200 millijoules per square centimeter;
[0153] Adjust the laser pulse duration to 20 nanoseconds;
[0154] Raise the temperature of the reaction chamber to 350 degrees Celsius and maintain a constant temperature;
[0155] Performing laser annealing on the gallium nitride device at the temperature for 7 minutes;
[0156] After the laser annealing treatment is completed, the temperature of the reaction chamber is lowered to room temperature.
[0157] Figure 2 The structure diagram of the manufacturing system for improving the reliability of gallium nitride transistors according to an embodiment of the present invention is as follows: Figure 2 As shown, the system comprises:
[0158] The first unit is used to select a high-purity sapphire substrate, and use chemical mechanical polishing technology to process the surface of the sapphire substrate to reduce the surface roughness of the sapphire substrate to less than 0.2 nanometers; then, in a vacuum environment, use a high-energy argon ion beam to bombard the surface of the sapphire substrate to form a nano-scale step structure, and the height of the nano-scale step structure is 2-5 nanometers; finally, use plasma enhanced chemical vapor deposition technology to deposit a layer of aluminum nitride buffer layer with a thickness of 10-20 nanometers on the surface of the sapphire substrate;
[0159] The second unit is used to place the pre-treated sapphire substrate in a metal organic chemical vapor deposition device, introduce trimethyl gallium and ammonia as precursors, and perform epitaxial growth of gallium nitride at a temperature of 900-1050 degrees Celsius; during the epitaxial growth process, an alternating pulse supply technology is adopted, that is, trimethyl gallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, and the iron doping concentration is controlled in the range of 1x10^15-5x10^16cm^-3 to reduce the background carrier concentration in the gallium nitride layer;
[0160] The third unit is used to form a source, a drain and a gate structure on the gallium nitride epitaxial layer by using photolithography and plasma etching techniques; then, a 5-10 nanometer thick hafnium oxide layer is deposited as a gate dielectric layer in the gate region by using atomic layer deposition technology; then, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the surface of the entire device by using plasma enhanced chemical vapor deposition technology; finally, the entire device is processed by using laser annealing technology, with a laser wavelength of 355 nanometers, an energy density of 100-300 mJ / cm^2, a pulse duration of 10-30 nanoseconds, and an annealing process carried out in a nitrogen atmosphere at a temperature of 300-400 degrees Celsius for 5-10 minutes to eliminate interface states and reduce leakage current.
[0161] According to a third aspect of the embodiments of the present invention,
[0162] An electronic device is provided, comprising:
[0163] processor;
[0164] a memory for storing processor-executable instructions;
[0165] The processor is configured to call the instructions stored in the memory to execute the aforementioned method.
[0166] According to a fourth aspect of the embodiments of the present invention,
[0167] A computer-readable storage medium is provided, on which computer program instructions are stored. When the computer program instructions are executed by a processor, the aforementioned method is implemented.
[0168] The present invention may be a method, an apparatus, a system and / or a computer program product. The computer program product may include a computer-readable storage medium carrying computer-readable program instructions for executing various aspects of the present invention.
[0169] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for improving the reliability of a gallium nitride transistor, characterized in that: include: A high-purity sapphire substrate is selected, and the surface of the sapphire substrate is processed by chemical mechanical polishing technology to reduce the surface roughness of the sapphire substrate to less than 0.2 nanometers; Subsequently, in a vacuum environment, a high-energy argon ion beam is used to bombard the surface of the sapphire substrate to form a nano-scale step structure, wherein the height of the nano-scale step structure is 2-5 nanometers; finally, a plasma enhanced chemical vapor deposition technique is used to deposit a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate; The pre-treated sapphire substrate is placed in a metal organic chemical vapor deposition device, trimethyl gallium and ammonia are introduced as precursors, and gallium nitride epitaxial growth is performed at a temperature of 900-1050 degrees Celsius; during the epitaxial growth process, an alternating pulse supply technology is adopted, that is, trimethyl gallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, and the iron doping concentration is controlled in the range of 1x10^15-5x10^16cm^-3 to reduce the background carrier concentration in the gallium nitride layer; On the gallium nitride epitaxial layer, photolithography and plasma etching techniques are used to form source, drain and gate structures; then, atomic layer deposition technology is used to deposit a 5-10 nanometer thick layer of hafnium oxide as a gate dielectric layer in the gate area; then, plasma enhanced chemical vapor deposition technology is used to deposit a 20-50 nanometer thick silicon nitride passivation layer on the surface of the entire device; finally, laser annealing technology is used to process the entire device, with a laser wavelength of 355 nanometers, an energy density of 100-300mJ / cm^2, a pulse duration of 10-30 nanoseconds, and an annealing process carried out in a nitrogen atmosphere at a temperature of 300-400 degrees Celsius for 5-10 minutes to eliminate interface states and reduce leakage current.
2. The method according to claim 1, characterized in that: Using plasma enhanced chemical vapor deposition technology, depositing a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate comprises: Introducing trimethylaluminum and ammonia as precursors into a reaction chamber, wherein the pressure of the reaction chamber is maintained at 20-30 mTorr, the radio frequency power is set to 200-300 watts, and the deposition temperature is set to 350 degrees Celsius; using pulse modulation technology to control the supply of the trimethylaluminum and the ammonia, wherein the supply ratio of the trimethylaluminum to the ammonia is 1:100, the pulse period is set to 2 seconds, the trimethylaluminum introduction time is 0.1 seconds, and the ammonia introduction time is 1.9 seconds; At the beginning of deposition, a nitrogen plasma with a power of 50 watts is used to treat the surface of the substrate for 30 seconds; by controlling the deposition time, an aluminum nitride buffer layer with a thickness of 10-20 nanometers is formed on the surface of the substrate; wherein the half-width of the (0002) crystal plane X-ray diffraction peak of the aluminum nitride buffer layer is less than or equal to 0.15 degrees, and the concentrations of carbon impurities and oxygen impurities in the aluminum nitride buffer layer are both lower than 1×10^18 cubic centimeters^-1, and when the thickness of the aluminum nitride buffer layer is 10 nanometers, the root mean square value of its surface roughness is 0.3 nanometers, and when the thickness of the aluminum nitride buffer layer is 20 nanometers, the root mean square value of its surface roughness is 0.5 nanometers.
3. The method according to claim 1, characterized in that During the epitaxial growth process, an alternating pulse supply technique is used, that is, trimethylgallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; At the same time, the introduction of trace amounts of iron doping during epitaxial growth includes: The pretreated substrate is transferred to a reaction chamber of a metal organic chemical vapor deposition device, the temperature of the reaction chamber is raised to 1000 degrees Celsius, and the pressure is controlled at 100 millibars; The epitaxial growth is carried out by using an alternating pulse supply technique, wherein trimethylgallium and ammonia are used as precursors, the supply cycle of the trimethylgallium and the ammonia is set to 1 second, the trimethylgallium introduction time is 0.3 second, the ammonia introduction time is 0.7 second, and a nitrogen purge of 0.1 second is introduced in the gap between the switching of the trimethylgallium and the ammonia; A trace amount of iron doping is introduced during the ammonia introduction stage, wherein the iron source is solid ferrocene, and the iron doping concentration is adjusted to 3×10^15 cubic centimeters^-1 by controlling the carrier gas flow rate and the source temperature; The surface reconstruction changes during the growth process were monitored by in situ reflection high energy electron diffraction, wherein a (2×2) reconstruction was observed during the trimethylgallium pulse and a (2×6) reconstruction was observed during the ammonia pulse; The growth process is controlled so that the half-height width of the (0002) crystal plane X-ray diffraction peak of the obtained GaN epitaxial layer does not exceed 180 arc seconds, the dislocation density is less than 1×10^8 cubic centimeters^-2, the background electron concentration at room temperature is 5×10^15 cubic centimeters^-3, and the electron mobility reaches 1800 square centimeters / volt·second; The distribution uniformity of the iron atoms in the depth direction of the gallium nitride epitaxial layer is controlled within ±10%.
4. The method according to claim 1, characterized in that Forming source, drain and gate structures on the gallium nitride epitaxial layer by using photolithography and plasma etching techniques includes: The surface of the GaN epitaxial layer was cleaned in three steps, using acetone, isopropanol and deionized water in sequence, with each step of ultrasonic cleaning lasting 5 minutes. After cleaning, the GaN epitaxial layer was placed on a hot plate at 120 degrees Celsius and baked for 10 minutes; The cleaned GaN epitaxial layer was spin-coated with positive photoresist AZ5214E at 4000 rpm for 30 seconds to obtain a photoresist film with a thickness of 1.4 μm, followed by soft baking at 90 degrees Celsius for 60 seconds; The GaN epitaxial layer coated with photoresist is exposed using a mask alignment exposure machine with an exposure dose of 120 mJ / cm2, and after exposure, reverse baking is performed at 110 degrees Celsius for 60 seconds, and then maskless sputtering exposure is performed with a dose of 200 mJ / cm2; Developed with AZ726 MIF developer for 40 seconds, rinsed with deionized water and dried with nitrogen gas to form a photolithography pattern with a minimum line width of 0.8 microns and an edge roughness of ±50 nanometers; An inductively coupled plasma etching system was used for selective etching of GaN, using a Cl2 / BCl3 / Ar gas mixture with a flow ratio of 20 / 10 / 5 standard cubic centimeters per minute, an inductively coupled plasma power of 500 watts, a bias power of 100 watts, and a chamber pressure of 5 mTorr; The etching depth was monitored in real time using laser interferometry endpoint detection technology. When the etching depth reached 200 nanometers, the etching was stopped and the GaN epitaxial layer was then transferred to an oxygen plasma chamber for 60 seconds of surface treatment. Using an electron beam evaporation system, a Ti / Al / Ni / Au metal stack is sequentially deposited on the etched GaN epitaxial layer with thicknesses of 30 / 120 / 40 / 50 nm, respectively, where Ti and Ni are deposited at a rate of 0.5 angstroms per second, Al is deposited at a rate of 1 angstrom per second, and Au is deposited at a rate of 1.5 angstroms per second; The GaN epitaxial layer after metal deposition was immersed in acetone for 5 minutes of ultrasonic stripping, and then rinsed with isopropanol and deionized water, and then annealed at 850 degrees Celsius for 30 seconds in a nitrogen atmosphere to form a source and drain structure; The above lithography steps were repeated, and a low-power oxygen plasma treatment of 30 s with a power of 30 W was performed on the gate area, followed by the deposition of Ni / Au metal stacks with thicknesses of 50 / 150 nm, respectively, to form the gate structure.
5. The method according to claim 1, characterized in that Using plasma enhanced chemical vapor deposition technology, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the entire device surface including: Pre-treatment of GaN transistors with oxygen plasma at 50 watts for 60 seconds to remove organic residues and oxides from the device surface; The pre-treated GaN transistor is placed in a sealed sample transfer box filled with high-purity nitrogen and transferred to the reaction chamber of the plasma enhanced chemical vapor deposition equipment; Silicon hydride and ammonia are introduced into the reaction chamber as precursor gases, and the flow ratio of silicon hydride to ammonia is controlled to be 1:4; The reaction chamber pressure was adjusted to 900 mTorr, the RF power was set to 50 W, and the substrate temperature was controlled at 300 degrees Celsius; The plasma enhanced chemical vapor deposition process was started, and the growth thickness of the silicon nitride film was monitored in real time using an in-situ ellipsometer; When the thickness of the silicon nitride film reaches 35 nanometers, the deposition process is stopped; The gallium nitride transistor with a silicon nitride film deposited thereon is slowly cooled down to room temperature at a rate of 5 degrees Celsius per minute; The silicon-nitrogen ratio of the silicon nitride film is 0.75±0.02, the root mean square value of the surface roughness is 0.3 nanometers, the Young's modulus is 220±10 GPa, and the hardness is 22±1 GPa.
6. The method according to claim 1, characterized in that The entire device is processed using laser annealing technology. The laser wavelength is selected to be 355 nanometers, the energy density is 100-300mJ / cm^2, the pulse duration is 10-30 nanoseconds, and the annealing process is carried out in a nitrogen atmosphere. The temperature is controlled at 300-400 degrees Celsius for 5-10 minutes to eliminate the interface state and reduce the leakage current, including: The GaN device with a silicon nitride passivation layer deposited thereon is placed in a reaction chamber with a high-purity nitrogen atmosphere, and the nitrogen flow rate is controlled to be 50 standard cubic centimeters per minute; An ultraviolet laser with a wavelength of 355 nanometers was used as the annealing light source, and the laser energy density was set to 200 millijoules per square centimeter; Adjust the laser pulse duration to 20 nanoseconds; Raise the temperature of the reaction chamber to 350 degrees Celsius and maintain a constant temperature; Performing laser annealing on the gallium nitride device at the temperature for 7 minutes; After the laser annealing treatment is completed, the temperature of the reaction chamber is lowered to room temperature.
7. A manufacturing system for improving the reliability of gallium nitride transistors, used to implement the method according to any one of claims 1 to 6, characterized in that: include: The first unit is used to select a high-purity sapphire substrate and process the surface of the sapphire substrate using a chemical mechanical polishing technology to reduce the surface roughness of the sapphire substrate to less than 0.2 nanometers; Subsequently, in a vacuum environment, a high-energy argon ion beam is used to bombard the surface of the sapphire substrate to form a nano-scale step structure, wherein the height of the nano-scale step structure is 2-5 nanometers; finally, a plasma enhanced chemical vapor deposition technique is used to deposit a 10-20 nanometer thick aluminum nitride buffer layer on the surface of the sapphire substrate; The second unit is used to place the pre-treated sapphire substrate in a metal organic chemical vapor deposition device, introduce trimethyl gallium and ammonia as precursors, and perform epitaxial growth of gallium nitride at a temperature of 900-1050 degrees Celsius; during the epitaxial growth process, an alternating pulse supply technology is adopted, that is, trimethyl gallium and ammonia are alternately introduced during the growth process, and each pulse period is 0.5-2 seconds; at the same time, a trace amount of iron doping is introduced during the epitaxial growth process, and the iron doping concentration is controlled in the range of 1x10^15-5x10^16cm^-3 to reduce the background carrier concentration in the gallium nitride layer; The third unit is used to form a source, a drain and a gate structure on the gallium nitride epitaxial layer by using photolithography and plasma etching techniques; then, a 5-10 nanometer thick hafnium oxide layer is deposited as a gate dielectric layer in the gate region by using atomic layer deposition technology; then, a 20-50 nanometer thick silicon nitride passivation layer is deposited on the surface of the entire device by using plasma enhanced chemical vapor deposition technology; finally, the entire device is processed by using laser annealing technology, with a laser wavelength of 355 nanometers, an energy density of 100-300 mJ / cm^2, a pulse duration of 10-30 nanoseconds, and an annealing process carried out in a nitrogen atmosphere at a temperature of 300-400 degrees Celsius for 5-10 minutes to eliminate interface states and reduce leakage current.
8. An electronic device, characterized in that: include: processor; a memory for storing processor-executable instructions; The processor is configured to call the instructions stored in the memory to execute the method according to any one of claims 1 to 6.
9. A computer-readable storage medium having computer program instructions stored thereon, characterized in that: When the computer program instructions are executed by a processor, the method according to any one of claims 1 to 6 is implemented.
Citation Information
Cited By
Intelligent sensor semiconductor wafer preparation method based on vapor deposition
CN120864805A
Method for the preparation of smart sensor semiconductor wafers based on vapor deposition
CN120864805B
Method for removing residual gallium on back surface of MicroLED chip
CN121487395A